To interleave or to block subtraction strategies? Strategy use- and error profiles among third graders - Nemeth, Lea; Lipowsky, Frank (Swiss Journal of Educational Research, 2021)
Primary students should learn how to solve subtraction tasks flexibly with different strategies. The current study therefore investigates students’ strategy proficiency by analyzing strategy use- and error profiles. A total of 236 third graders were taught using subtraction strategies in an interleaved or blocked fashion. A latent transition analysis revealed five strategy choice- and error profiles. Prior to the intervention, most students primarily used the stepwise strategy with only few errors. After the intervention, most of the students were flexible calculators with very few errors, followed by those primarily using the written algorithm with few errors. Students’ prior knowledge and being taught interleaved subtraction had a positive influence on the transition to the profile of flexible strategy use.